A RANDOMIZED CONTROLLED CROSS-OVER TRIAL OF STANDARD ITALIAN PROTOCOL VERSUS FRONT-LOADED GLYCERYL TRINITRATE HEAD-UP TILT TEST - Irfan, Muhammad; Shabbir, Muhammad; Zahid, Maham; Hayat, Azmat; Majeed, Syed Muhammad Imran (Pakistan Armed Forces Medical Journal, 2015)
Objective: To evaluate the sensitivity, specificity, and accuracy of front loaded glyceryl trinitrate head-up tilt test as a first line investigation. Study Design: Randomized cross-over trial. Place and Duration of Study: This study was conducted at electrophysiology department AFIC/NIHD Rawalpindi. Patients presenting with syncope in the month of Dec 2014 were enrolled in the study. Material and Methods: Forty four consecutive patients between ages 14-70 years presenting to AFIC for investigation of unexplained syncope were enrolled in this study and were randomized to either of a protocol via sealed envelope method. All of the participants were then crossed-over to the opposite protocol at least one week apart. Results: For protocol A, there were 28 positive responses (63.3%) and 17 (38.6%) for protocol B. There was no statistically significant difference between the outcomes of protocol A and protocol B (p-value 0.001). Protocol B is as specific (93.75%) as standard Italian method but less sensitive (57.14%) than standard Italian protocol. The time at which positive response occurred during the provocation phase of protocol A and B is 7.2 ± 3.6 vs 9.0 ± 3.5 minutes respectively, which is not significantly different (p value = 0.177, 95% CI = -1.4 – 0.88). Conclusion: Although front-loaded glyceryl trinitrate protocol is equal in specificity with the standard Italian protocol, it has a greater number of false-negative results.